Factor structure of the Behavior Rating Inventory of Executive Functions (BRIEF-P) at age three years. Issue 4 (18th May 2016) - Skogan, Annette Holth; Egeland, Jens; Zeiner, Pål; Øvergaard, Kristin Romvig; Oerbeck, Beate; Reichborn-Kjennerud, Ted; Aase, Heidi
Abstract : The preschool period is an important developmental period for the emergence of cognitive self-regulatory skills or executive functions (EF). To date, evidence regarding the structure of EF in preschool children has supported both unitary and multicomponent models. The aim of the present study was to test the factor structure of early EF as measured by the Behavior Rating Inventory of Executive Function-Preschool version (BRIEF-P). BRIEF-P consists of five subscales and three broader indexes, hypothesized to tap into different subcomponents of EF. Parent ratings of EF from a nonreferred sample of children recruited from the Norwegian Mother and Child Cohort Study ( N = 1134; age range 37–47 months) were subjected to confirmatory factor analyses (CFA). Three theoretically derived models were assessed; the second-order three-factor model originally proposed by the BRIEF-P authors, a "true" first-order one-factor model and a second-order one-factor model. CFA fit statistics supported the original three-factor solution. However, the difference in fit was marginal between this model and the second-order one-factor model. A follow-up exploratory factor analysis (EFA) supported the existence of several factors underlying EF in early preschool years, with a considerable overlap with the five BRIEF-P subscales. Our results suggest that some differentiation in EF has taken place at age 3 years, which is reflected in behavior ratings. The internal consistency of the BRIEF-P five clinical subscales is supported. Subscale interrelations may, however, differ at this age from those observed in the preschool group as a whole.